Prevalence of Synchronous Oligopolyposis in Incident Colorectal Cancer: A Population-Based Study - Marqués-Lespier, Juan M.; Soto-Salgado, Marievelisse; González-Pons, María; Méndez, Vanessa; Freyre, Katerina; Beltrán, Carlos; Pericchi, Luis R.; Cruz-Correa, Marcia (Puerto Rico Health Sciences Journal, 2018)
Objective: Colorectal cancer (CRC) is a leading causes of cancer death among men and women. The purpose of this study was to determine the prevalence of oligopolyposis (≥20 synchronous colorectal adenomas) and its associated clinicopathological characteristics in Hispanics with incident CRC. Methods: Pathology reports from individuals diagnosed with CRC (2007 to 2011) were obtained from the PR Central Cancer Registry. Colorectal polyp burden was calculated using pathology reports and the data was normalized to colon segment size. Comparisons of demographic and clinicopathological characteristics by synchronous oligopolyposis status (<20 vs. ≥20) were performed using the chi-square or Fisher’s exact test. Multivariate logistic regression models were fitted to estimate the adjusted prevalence odds ratios (aPOR), with 95% confidence intervals (CI). All analyses were performed using Stata (v.12.0). Results: Analyses of 1,573 colectomy specimens was performed. Oligopolyposis was observed in 9.47% (149 of 1,573) of the subjects with incident CRC. Increasing age (aPOR50–64 = 1.72, 95% CI: 0.59–5.02; aPOR65–74 = 1.83, 95% CI: 0.64–5.27; aPOR≥75 = 2.67, 95% CI: 0.93–7.64) and proximal CRC tumor location (POR = 2.91, 95% CI: 1.98–4.30) were significantly associated with having oligopolyposis at CRC diagnosis. However, subjects diagnosed with CRC at a regional stage (aPORRegional = 0.50, 95% CI: 0.32–0.79) or distant stage (aPORDistant = 0.45, 95% CI: 0.29–0.69) were less likely to have synchronous oligopolyposis (p<0.05). Conclusion: Our findings suggest that genetic syndromes associated with colorectal polyposis may be implicated in a higher than expected number of CRC cases. Individuals with CRC and synchronous oligopolyposis should receive genetic counseling.